Knowledge of endotracheal suctioning among critical care nurses in teaching hospital intensive care unit, Malaysia - Abdul Halain, Azura; Yusof, Sukini; Ibrahim, Airini; Soh, Kim Geok; Abdul Raman, Rosna; Japar, Salimah; Soh, Kim Lam (Medknow Publications and Media, 2021)
Endotracheal suctioning (ETS) is an intervention to remove accumulated mucus from the endotracheal tube, trachea, and lower airways in patients who require intubation. This intervention creates a large variety of heart-lung interferences which will cause serious complications to patients such as hypoxaemia, raised blood pressure, raised intracranial pressures and pneumothorax. It is imperative that nurses are aware of these risks and are able to practice according to current research recommendations. The main objective of this study is to explore nurses’ knowledge to ETS. This is cross sectional studied by using self-administered questionnaire for nurse’s knowledge in performing endotracheal suction to ICU patients.Data collection involving 127 nurses in ICUs. The results of this study showed that a majority of the nurses were knowledgeable about ETS with a mean score of 71.7±SD10.8. This study has also raised interesting issues concerning multiple aspects of endotracheal suctioning among the Critical care nurses (CCNs) and the results indicate the needs for teaching intervention to improve knowledge of ETS.